ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN PENDAPATAN DI PULAU JAWA - Muhammad Farhan (2021)
Inequality is one of the obstacles in economic development in every country. The difference in income seems to make the distance between the rich and poor groups increase considerably and welfare is still unevenly distributed between the upper and lower classes of society. This study aims to identify and analyze the factors that influence income using data from 6 provinces in Java for the period 2014-2020. The method used in this study is a panel data regression model with the selected model is the Fixed Effect Model (FEM). The results of this study indicate that (1) it has no effect on income in Java (2) does not affect the increase in income in Java (3) has no effect on increasing income in Java